PENGARUH PENGGUNAAN MODEL GROUP INVESTIGATION (GI) DAN PENGUASAAN KOSAKATA TERHADAP KETERAMPILAN MENULIS TEKS NEGOSIASI PADA SISWA KELAS X SMA NEGERI 1 NGAWI TAHUN AJARAN 2021/2022 - Christiana, Tety Martha (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2022)
This study aims to test the difference in the writing skills of negotiating texts between students who are taught with the group investigation model and students who are taught with discovery learning models (as control) in class X students of SMA Negeri 1 Ngawi. The sample in this study was from class X MIPA 1 SMA Negeri 1 Ngawi with the number of students 36 children and from class X MIPA 2 with the number of students 36 children with two stage random sampling techniques. This study uses an experimental method with a factorial design of 2x2. Data collection is carried out with written test techniques for data writing negotiation skills. Data analysis using techniques: (1) descriptive data analysis; (2) test requirements; and (3) statistically inferential data analysis using two-way anava techniques. The results of this study indicate that there are significant differences in student negotiation text writing skills between the Group Investigation (GI) model and the Discovery Learning (DL) model (FA = 72.29 > F0,05;1;68 = 3.98). Students with the Group Investigation learning model has better result than students with discovery learning learning models. Keywords: Group Investigation, Discovery Learning, Writing Skills, Negotiations Text